+COMPARATIVE ACCOUNT OF GROWTH RATE 0f BODY PARTS WITH TOTAL LENGTH IN ADULT PUNTIUS SARANA (HAM.) - KUMAR, S.; DUTT, S. (Journal of Indian Fisheries Association, 2015)
The present study on growth rate of different body pa~ts in relation tototal length, in the male and female Puntius sara.na (Ham.) did not show anysignificant heterogeneity except in snout length (p.Ol). The growth rate ofsnout length was found to be higher in females (b~0.0377) than in males(b=0.0266). Since the growth rate of most of the body parts was found to behomogeneous in both the sexes, the common regression co-efficient ''b" werecalculated on pooled data to represent the growth rate of different bodyparts against total length, The linearity of regression lines indicated isomertircgrowth.Keywords: Growth rate, Puntius, morphometry